Molecular dynamics simulation of Al–Co–Cr–Cu–Fe–Ni high entropy alloy thin film growth. (January 2016) - Xie, Lu; Brault, Pascal; Thomann, Anne-Lise; Yang, Xiao; Zhang, Yong; Shang, GuangYi
Abstract: Molecular dynamics (MD) simulations are used to study AlCoCrCuFeNi high entropy alloy (HEA) thin film growth on a silicon (100) substrate. Effect of the atomic composition is studied on morphology and atomic scale structure. Input data are chosen to fit with experimental operating conditions of magnetron sputtering deposition process. It is observed that the different structures are determined by the chemical composition and atomic size mismatch. The simulated results are in good agreement with the solid-solution formation rules proposed by Zhang et al. [1] for multi-principal component HEAs which based on the two parameters δ and Ω, respectively describing describe the comprehensive effect of the atomic-size difference in the n-element alloy and the effects of enthalpy and entropy of mixing on formation of multi-component solid-solutions. When Ω ≥ 1.1 and δ ≤ 6.6%, the multi-component solid solution phase could form. In contrast, the multi-component alloys forming intermetallic compounds and bulk metallic glasses (BMG) have larger value of δ and smaller value of Ω. The value of Ω for BMG is smaller than that of intermetallic compounds. Highlights: AlCoCrCuFeNi high entropy alloy thin film growth on silicon (100) substrate using MD simulation. Chemical composition and atomic size mismatch have significant effects on the atomic configuration. The simulated results are in good agreement with the solid-solution formation rules.